High-Resolution Image and Video CubeSat (HiREV): Development of Space Technology Test Platform Using a Low-Cost CubeSat Platform - Dong-Hyun Cho; Won-Sub Choi; Min-Ki Kim; Jin-Hyung Kim; Eunsup Sim; Hae-Dong Kim (International Journal of Aerospace Engineering)
In this paper, we present high-resolution image and video CubeSat (HiREV), the first constructed 6 U platform to reach the space technology test bed stage, developed by the Korea Aerospace Research Institute (KARI). The CubeSat system is a low-cost platform that has been widely applied to various space missions, from missions involving earth observation to deep space. Despite the emergence of the CubeSat technology worldwide, the CubeSat market in Korea is still in the beginning stages, and a standard testing platform is also in demand. For this reason, KARI is starting to develop a 6 U CubeSat platform, which includes a less than 3 U bus system and greater than 3 U payload space. HiREV has been developed with locally manufactured parts, creating a domestic commercial off-the-shelf infrastructure for CubeSat and 3 m resolution camera payload development. Core flight software has also been applied as an on-board flight software system. Presently, we have developed the main system, while HiREV is under space environmental testing.